Flying Without Wings - Rishabh Puri (Harpercollins, 2017)
For Milli Bajwa, life is at a stand-still. Grounded in the Chandigarh airport where she works day after day, she watches flights leaving for destinations she knows she ll never visit. Loveless and luckless, she would rather bury her nose in a book than face her grim reality. And then, on a whim, she swipes right on a new dating app, and finds the man of her dreams someone who can sweep her off her feet and teach her how to fly. But the mysterious and charming Karan Singhania has secrets of his own, and a heart damaged in more ways than one. This is the story of two people about to find out how far they re willing to go for the promise of true love. Will Karan take a chance and dive blind-folded and headfirst towards his dreams? Will Milli be willing to stand by Karan s side in sickness and in health, just for a glimpse of his smile? This is a story of hope and joy in times of heartache and trial. Of finding the perfect person in imperfect situations. And of love s power to carry us through our darkest times.